The knowledge and perceptions regarding antibiotic stewardship of the interns rotating at the Bloemfontein Academic Complex - Anke Archer; Marna Blom; Renette de Lange; Esther Jansen van Vuuren; Theunis E. Kellerman; Samantha Potgieter; Gina Joubert (South African Family Practice)
Background: Antibiotic resistance (ABR) is a global problem with the overuse of antibiotics accelerating this process. Antibiotic stewardship aims to optimise antibiotic treatment to enable cost-effective therapy and improve patients’ outcome whilst limiting ABR. The study aimed to evaluate intern medical doctors’ knowledge and perceptions about antibiotic stewardship and their perceptions regarding education on relevant topics.